Between science and local knowledge: improving the communication of climate change to rural agriculturists in the Bolgatanga Municipality, Ghana. Issue 3 (4th March 2019) - Anaafo, David
ABSTRACT: There is an overwhelming scientific consensus that global climate is changing with associated devastating, yet differential impacts on different world regions. This, therefore, calls for efforts to improve our understanding of the phenomenon as a way of enhancing mitigation and adaptation measures. Although a lot has been done in this respect, the present study examines the extent to which misnomers associated with the calendar months and local climate events can be employed to convey the phenomenon of climate change to rural agriculturists in the Bolgatanga municipality. The study establishes that the names of the calendar months, which serve as goalposts for local agricultural practices no longer portray their true meaning due to climate change. The study, therefore, recommends the use of nuanced ways of communicating climate change to local agriculturists, using scientific research, lived experiences as well as socially and culturally embedded tools such as misnomers associated with local climate events.